A new catalyst for the solvent-free conversion of CO2 and epoxides into cyclic carbonate under mild conditions. (June 2016) - Yu, Shuai-Shuai; Liu, Xiao-Huan; Ma, Jian-Gong; Niu, Zheng; Cheng, Peng
Graphical abstract: Highlights: A new Cu6 cluster with high density of active Lewis acid sites was synthesized. The cluster acts a good catalyst for the fixation of CO2 into cyclic carbonates. The preparation of the cluster is very simple and rapid with low cost. Abstract: A new Cu6 cluster [Cu6 (μ4 -O)2 (SO4 )4 (DMA)6 ] (1 ) with high density of active Lewis acid sites turns out to be a good catalyst for the chemical fixation of CO2 into value-added cyclic carbonates without the use of any organic solvents under room temperature and atmospheric pressure. Above all, the preparation of1 is very simple and rapid with low cost, which has important implications for industrial applications.